2015
DOI: 10.1111/jnc.13101
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of peroxisome proliferator‐activated receptors (PPAR) α and ‐γ of rat brain astrocytes in the course of activation by toll‐like receptor agonists

Abstract: Peroxisome proliferator-activated receptors (PPAR)-a and -c in astrocytes play important roles in inflammatory brain pathologies. Understanding the regulation of both activity and expression levels of PPARs is an important neuroscience issue. Toll-like receptor (TLR) agonists are inflammatory stimuli that could modulate PPAR, but the mechanisms of their control in astrocytes are poorly understood. In the present study, we report that lipopolysaccharide, peptidoglycan, and flagellin, which are agonists of TLR4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 52 publications
0
23
1
4
Order By: Relevance
“…Although we failed to observe an anti‐inflammatory effect of GW0742 in iPSC‐astrocytes, others have reported that PPARβ/δ activation alleviates astrocytic pro‐inflammatory activation (Chistyakov, Aleshin, Astakhova, Sergeeva, & Reiser, ). In contrast, the impact of GW0742 on suppression of inflammation may be model dependent, as Schnegg et al reported that GW0742 inhibited neuroinflammation, yet failed to restore neurogenesis or prevent hippocampal dependent cognitive deficits (Schnegg et al, ).…”
Section: Discussioncontrasting
confidence: 84%
“…Although we failed to observe an anti‐inflammatory effect of GW0742 in iPSC‐astrocytes, others have reported that PPARβ/δ activation alleviates astrocytic pro‐inflammatory activation (Chistyakov, Aleshin, Astakhova, Sergeeva, & Reiser, ). In contrast, the impact of GW0742 on suppression of inflammation may be model dependent, as Schnegg et al reported that GW0742 inhibited neuroinflammation, yet failed to restore neurogenesis or prevent hippocampal dependent cognitive deficits (Schnegg et al, ).…”
Section: Discussioncontrasting
confidence: 84%
“…Toll-like receptor (TLR) agonists reduce the mRNA, protein levels and activity of PPARγ, which is crucial for inflammation response in rat brain astrocytes [30]. These existing researches leaded us to investigate whether reciprocation between PPARγ and TLR4 contributed to inflammation in LPS-stimulated endothelial EA.hy926 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of proinflammatory factors on NF-κB is accompanied by the synthesis of prostaglandins D2 and E2 (PGD2 and PGE2) activating PPARα and PPARγ. C-Jun-NH2-terminal kinase (JNK) and p38 mitogen-activated protein kinase (P38MAPK), which are members of the signaling pathways of mitogenactivated protein kinase (MAPK) cascades, are involved in the regulation of PPAR expression [49,50]. Activated PPARs (all isoforms) inhibit NF-κB activity, leading to the suppression of inflammation.…”
Section: Ppar Researchmentioning
confidence: 99%